2013
DOI: 10.1242/dev.092882
|View full text |Cite
|
Sign up to set email alerts
|

Divergent roles for Wnt/β-catenin signaling in epithelial maintenance and breakdown during semicircular canal formation

Abstract: SUMMARYThe morphogenetic program that shapes the three semicircular canals (SSCs) must be executed with extreme precision to satisfy their complex vestibular function. The SSCs emerge from epithelial outgrowths of the dorsal otocyst, the central regions of which fuse and resorb to leave three fluid-filled canals. The Wnt/β-catenin signaling pathway is active at multiple stages of otic development, including during vestibular morphogenesis. How Wnt/β-catenin functionally integrates with other signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 48 publications
4
39
0
Order By: Relevance
“…CHIR appears to have little effect on ESC-derived aggregates when it is applied to the aggregates before Pax8 expression (Fig 2E). This is consistent with inner ear development in vivo where Wnt signaling appears to be necessary for otic placode induction after specification of the broader Pax8+ otic-epibranchial progenitor domain [15, 34]. As in inner ear development, in which Wnt ligands are thought to diffuse from the neural tube between embryonic days 7.5–8.5, our model appears to have a temporal window for Wnt activation in which otic induction is optimal [6, 3538].…”
Section: Discussionsupporting
confidence: 81%
“…CHIR appears to have little effect on ESC-derived aggregates when it is applied to the aggregates before Pax8 expression (Fig 2E). This is consistent with inner ear development in vivo where Wnt signaling appears to be necessary for otic placode induction after specification of the broader Pax8+ otic-epibranchial progenitor domain [15, 34]. As in inner ear development, in which Wnt ligands are thought to diffuse from the neural tube between embryonic days 7.5–8.5, our model appears to have a temporal window for Wnt activation in which otic induction is optimal [6, 3538].…”
Section: Discussionsupporting
confidence: 81%
“…In mice, disruption of the RA-synthesising enzyme gene Raldh3 results in both morphological and functional deficits of the entire vestibular system [45]. Another study in mice has demonstrated the importance of Wnt/b-catenin signalling in sculpting the semicircular canal ducts via regulation of Netrin1-mediated cell resorption at the canal fusion plate [46].…”
Section: Semicircular Canal Morphogenesismentioning
confidence: 99%
“…The anterior and posterior canals stained more uniformly when tamoxifen was administered at or prior to E10.5, compared to later stages when Wnt/β-catenin signaling activity becomes more restricted (Fig. 2A–F; Rakowiecki and Epstein, 2013). The lateral canal labeled sparsely throughout these experiments due to the limited expression of Cre on the dorsolateral side of the otocyst, the region from where progenitors of this canal originate (Morsli et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…It is intriguing to speculate that the canonical Wnt signaling pathway, which is essential for vestibular morphogenesis and sensory cristae specification at early stages of otic development (Riccomagno et al, 2005; Rakowiecki and Epstein, 2013), was appropriated for additional use to facilitate the ventral displacement of prosensory progenitors along the medial wall of the cochlear duct. This model provides a compelling explanation for why Wnt1 −/− ; Wnt3a −/− double mutants exhibit cochlear outgrowth defects, despite the selective loss of Wnt signaling activity in dorsal otic regions (Riccomagno et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation